Slow Violence and Water Racism in Sarnath Banerjee’s All Quiet in Vikaspuri - Madan, Anuja (My University, 2018)
This paper claims that Sarnath Banerjee destabilizes the narrative of national economic progress in his graphic narrative All Quiet in Vikaspuri by highlighting ecological crises and destruction of communities in India. The graphic narrative makes visible the slow violence of ecological destruction and mass displacement triggered by neoliberalism. It shows that the sharp inequality in access to water in Delhi entails a denial of hydraulic citizenship to refugees and the poor. The only solution to this crisis, the text suggests, is water democracy and resistance against neoliberal monopolies. The working-class hero’s alliance with erstwhile water criminals – one which transcends ethnicity and class – is illustrative of how social justice may be achieved. However, I argue that the underrepresentation of women in the graphic narrative is a significant limitation of the text, especially since it inadvertently perpetuates the invisibility of women prevalent in development models.
Citation: Anuja Madan (2018) Slow Violence and Water Racism in Sarnath Banerjee’s All Quiet in Vikaspuri, South Asian Review, 39:1-2, 125-143, DOI: 10.1080/02759527.2018.1509548
Keywords: Indian graphic narratives; Neoliberalism; Water crisis; Ecological destruction; Slow violence; Citizenship